Pengaruh Motivasi, Pemahaman, Sikap, Norma Subjektif, Kontrol Perilaku Persepsian Terhadap Niat Mahasiswa Akuntansi Untuk Mengikuti Sertifikasi Akuntan Profesional Chartered Accountant (CA) - Adiva Salsabila; Rieska Maharani; Ma'ruf Sya'ban (UMSurabaya Publishing, 2022)
The Influence of Motivation, Understanding, Attitudes, Subjective Norms, and Perceived Behavioral Control on the Intention of Accounting Students to Take Chartered Accountant (CA) Professional Accountant Certification. A person is considered a professional as evidenced by a professional certification. The purpose of this study was to determine the influence of motivation, understanding, attitudes, subjective norms and perceived behavioral control on the intention of accounting students to take the Chartered Accountant (CA) professional accountant certification. This study uses quantitative methods with an explanatory research approach. The population used were undergraduate accounting students at University of Muhammadiyah Surabaya, STIESIA Surabaya, Airlangga University Surabaya, and the National Development University